Perancangan Sistem Estimasi Biaya Proyek Pengembangan Software - Suharjito Suharjito; Agus Widodo; Budi Prasetyo (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
A project software is categorized as successful if that project is delivered on time, within the specified budget, and having the expected quality. To achieve those goals, a project manager must be able to estimate realistic cost and effort for the project. However, the complex and intangible characteristics of software project cause difficulties in estimating the software project. The purpose of this research is to devising a system estimate expense and effort development project of software have matching with condition in the country. The developed estimation model in this study is a parametric method which uses local data so that it could yield higher validity for local software projects. The steps undertaken in this study are literature study, data analysis, mathematic modeling, implementation and testing. The conclusion is this application applicable to estimate expense and effort project of software with characteristic of information system by using function points metric.Keyword: project, software, Metrik Function Point, model, estimate realistic cost and effort